Relating sinking and suspended microbial communities in the California Current Ecosystem: digestion resistance and the contributions of phytoplankton taxa to export. (30th August 2021) - Valencia, Bellineth; Stukel, Michael R.; Allen, Andrew E.; McCrow, John P.; Rabines, Ariel; Palenik, Brian; Landry, Michael R.
Summary: We used 16S, 18S, plastid and internal transcribed spacer (for Synechococcus strains) sequencing to quantify relative microbial abundances in water‐column samples and on sediment‐trap‐collected particles across an environmental gradient in the California Current Ecosystem (CCE) spanning a > 60‐fold range of surface chlorophyll. Most mixed‐layer dominant eukaryotes and prokaryotes were consistently underrepresented on sinking particles. Diatoms were the only phototrophic taxa consistently overrepresented. Even within this class, however, one genus ( Thalassiosira ) was a particle‐enriched dominant, while a similarly abundant species was poorly represented. Synechococcus was significantly enriched on sinking particles at only one of four sites, but clade I was disproportionately abundant on sinking particles throughout the region compared with clade IV, the euphotic‐zone co‐dominant. The most abundant microbes on particles across the CCE were organisms with distributional maxima close to the sediment‐trap depth (rhizarians), microbes associated with metazoans or sinking particles as a nutritional habitat (certain alveolates, Gammaproteobacteria) and organisms that resist digestive degradation of their DNA ( Thalassiosira, Synechococcus ). For assessing taxon contributions of phytoplankton to carbon export, our results highlight the need for sequence‐based quantitative approaches that can be used to integrate euphotic‐zone abundances, compute rates and account for taxon differences in preservation of sequence markers through trophic processing.